Comparison of the reproducibility of 2D doppler and 3D stic in the measurement of fetal cardiac output. (7th June 2011) - Parasuraman, R; Osmond, C; Howe, D T
Abstract : Objectives: Two methods have been described to assess fetal cardiac output (CO). It has usually been assessed using Doppler to measure flow velocity and 2D ultrasound measurement of outflow valve diameter. Recently CO has been assessed using 3D spatio-temporal image correlation (STIC) to measure stroke volume. We aimed to compare the reproducibility of these techniques. Methods: In 27 women with singleton pregnancies, examinations were performed in three gestational age groups: 13–15, 19–21 and >30 weeks of gestation. Each mother was scanned once. Using 2D pulsed wave Doppler the duration and average flow velocity in systole was measured through aortic and pulmonary valves. We averaged values from three consecutive Doppler complexes. The outlet valve diameter was measured and the CO was calculated for each valve. The measurements were repeated to assess reproducibility. In the same women, we acquired STIC volumes of the fetal heart. The volume measurements were made using the 3D Slice method by one observer. Using 2 mm slices the circumference of the ventricles was traced at the end of systole and diastole to calculate ventricular volume before and after contractions to calculate stroke volume and hence CO. The measurements were repeated to assess reproducibility. Results: The root mean square difference of log (CO) of repeat measurements ranged between 0.12 and 0.21 using Doppler compared to 0.7 to 1.47 using STIC. Conclusions: We found that Doppler assessment of fetal cardiac output was more reproducible than measurement using STIC.